The crystal structure of the selenide-based synthetic sulfosalt CuPbSb3Se6 - Paul Sicher; Berthold Stöger (Acta Crystallographica Section E: Crystallographic Communications, 2023)
Single crystals of copper lead triantimony hexaselenide, CuPbSb3Se6, were obtained as a minor phase during systematic studies of the formation conditions of selenide-based sulfosalts. The crystal structure is an unusual representative of the family of sulfosalts. Instead of the expected galena-like slabs with octahedral coordination, it features mono and double-capped trigonal–prismatic (Pb), square-pyramidal (Sb) and trigonal–bipyramidal (Cu) coordination. All metal positions are occupationally and/or positionally disordered.